Research progress in the role of β-arrestin 1 in the regulation of inflammatory response - YI Wenjing; FAN Yixuan; QIU Jiatai; FU Xiaoyan; LIU Meifang (Shanghai Jiaotong Daxue xuebao. Yixue ban)
The inflammatory response is a systemic process produced by the body in response to stimulation such as infection or injury. The inflammatory response is closely related to the pathogenesis of various diseases, and plays an important role in the progression and outcome of diseases. Under normal conditions, the inflammatory response can maintain tissue homeostasis when the body is not seriously damaged. However, an uncontrolled inflammatory response that occurs when the body is subjected to more severe stimuli may often cause serious harm to the body. The termination of the ideal inflammatory response occurs after the elimination of the inflammatory stimulus. Therefore, it is particularly important to effectively modulate the extent and scope of the inflammatory response. β-arrestin 1 (ARRB1) is a multifunctional regulatory protein that plays a key role in G protein-coupled receptor (GPCR) and non-GPCR-mediated signal transduction. Meanwhile, this protein also participates in the regulation of some immune cell development, differentiation and other functions. Although ARRB1 was originally thought to be a terminator of GPCR signal transduction and can inhibit the inflammatory response, recent studies suggest that its role in inflammatory responses is complex, with dual anti-inflammatory and pro-inflammatory effects. Based on this, this article reviews the relevant research on ARRB1 and the inflammatory response in recent years, focusing on the regulatory role of ARRB1 in signaling pathway transduction and immune cell development and differentiation function, as well as its mechanism of action in regulating the progression of inflammatory diseases, in order to provide new insights for the clinical precision treatment of inflammatory diseases and the screening of drug effect targets.